Effect of NAC treatment and physical activity on neuroinflammation in subchronic Parkinsonism; is physical activity essential? - Ana-Luisa Gil-Martínez; Lorena Cuenca; Consuelo Sánchez; Cristina Estrada; Emiliano Fernández-Villalba; María Trinidad Herrero (Journal of Neuroinflammation, 2018)
Abstract Background Neuroprotective strategies are becoming relevant to slow down dopaminergic cell death and inflammatory processes related to the progressive neurodegeneration in Parkinson’s disease (PD). Interestingly, among others, physical activity (PA) or anti-oxidant agents (such as N-acetyl-L-cysteine, NAC) are common therapeutic strategies. Therefore, this study aims to analyze if there is a synergistic effect of physical activity along with NAC treatment on dopaminergic degeneration and neuroinflammatory response in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinsonism model after subchronic intoxication. Methods To ascertain this possibility, 48 8-week-old male mice (C57BL/6 strain) were used. Twenty four of them were placed individually in cages where voluntary physical activity was automatically monitored during 30 days and were divided into groups: (i) control; (ii) NAC; (iii) MPTP, and (iv) MPTP+NAC. The other 24 mice were divided into the same four groups but without physical activity. Results The data collected during the treatment period showed that there was an overall increase in the total running distance in all groups under physical activity, including Parkinsonian animals. However, the monitoring data per day showed that the activity routine by MPTP and MPTP+NAC groups was disrupted by alterations in the circardian rhythm because of MPTP intoxication. Results from post-mortem studies in the substantia nigra pars compacta (SNpc) showed significant decrease in the number of TH+ cells in all MPTP groups. Moreover, TH+ expression in the striatum was significantly decreased in all MPTP groups. Thus, PA + NAC treatment do not protect dopaminergic neurons against a subchronic intoxication of MPTP. Regarding glial response, the results obtained from microglial analysis do not show significant increase in the number of Iba-1+ cell in MPTP+NAC and MPTP+PA + NAC. In the striatum, a significant decrease is observed only in the MPTP+NAC group compared with that of the MPTP group. The microglial results are reinforced by those obtained from the analysis of astroglial response, in which a decrease in the expression of GFAP+ cells are observed in MPTP+NAC and MPTP+PA + NAC compared with MPTP groups both in the SNpc and in the striatum. Finally, from the study of the astroglial response by the co-localization of GFAP/S100b, we described some expression patterns observed based on the severity of the damage produced by the MPTP intoxication in the different treated groups. Conclusions These results suggest that the combination of physical activity with an anti-oxidant agent does not have a synergistic neuroprotective effect in the nigrostriatal pathway. Our results show a potential positive effect, only due to NAC treatment, on the neuroinflammatory response after subchronic MPTP intoxication. Thus, physical activity is not essential, under these conditions. However, we believe that physical activity, used for therapeutic purposes, has a beneficial long-term effect. In this line, these results open the door to design longer studies to demonstrate its promising effect as neuroprotective strategy.